Based on the Parameters of the Combined Agricultural Plastic for Field Crops - Norchaev Davron Rustamovich; Nigmatjonov Sardor Abdumannobivich (Genius Journals, 2023)
In the article the construction scheme of the machine that drops the agricultural plastic on the fields suitable for climatic conditions has been developed in Uzbekistan and also its main parameters are based on theoretical science and their values are determined according to theoretical expressions. According to the results of this theoretical research, it is possible to create an experimental model of the machine.
Keywords: combined agricultural plastic mat; a field; a crop; an elastic pipe hanger